2000
DOI: 10.1046/j.1365-2672.2000.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific restriction endonucleases in cyanobacteria

Abstract: Aim: Planktic cyanobacteria were screened for endodeoxyribonucleases. Principal component analysis (PCA) was employed to demonstrate a potential relationship between certain enzymes and a group of cyanobacteria. The data were obtained from a data bank and this study. Methods and Results: Enzymes were partially purified using column chromatography. Anabaena strains contained Asp83/1I (5′‐TTCGAA‐3′), Asp83/1II (5′‐GGCC‐3′), Asp90I (5′‐ACRYGT‐3′) and five isoschizomeric enzymes (5′‐ATCGAT‐3′). Aphanizomenon and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Generally, only one or two REases were found in each strain of cyanobacteria through conventional methods to test the crude cell extracts for their restriction activity (29,37). The main reason is the difficulty of detecting Type I RMs or solitary DNA MTases by biochemical or genetic assay (34,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, only one or two REases were found in each strain of cyanobacteria through conventional methods to test the crude cell extracts for their restriction activity (29,37). The main reason is the difficulty of detecting Type I RMs or solitary DNA MTases by biochemical or genetic assay (34,41).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional method used to screen for REases is to culture individual strains and test their extracts for the ability to produce specific fragments from small DNA molecules (55). A large number of both filamentous and unicellular cyanobacteria have been shown to contain one or more Type II site-specific REases (29). Lyra et al (29) employed principal component analysis to demonstrate the relationship between certain REases and their hosts and found that all 28 cyanobacterial strains studied contain Type II REases, with the most common cyanobacterial REase types being AvaII, AvaI, and AsuII.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been attributed to its stringent restriction modification system, as well as possible extracellular nucleases that degrade incoming DNA (10,20,42). Although mutants of Tfp genes in M. aerguinosa PCC 7806, including pilT, are currently under investigation to confirm the functionality of its Tfp system, subsequent confirmation of transformability is a substantial hurdle given the low transformation efficiency of M. aeruginosa PCC 7806, as well as its relatively low growth rate (division time, approximately 24 h).…”
Section: Discussionmentioning
confidence: 99%
“…The methylase protects the self DNA from restriction digestion by methylating the nucleotides at specific DNA sequences (i.e., restriction sites), while the foreign DNA, which usually bears a different methylation pattern, would be recognized and degraded by the endonucleases (18). It has been reported that R-M systems can dramatically reduce the DNA transformation efficiency in a variety of bacteria (13,(19)(20)(21)(22)(23)(24), including cyanobacteria (7,(25)(26)(27)(28). For instance, Elhai and coworkers reported that the efficiency of conjugal transfer of shuttle vectors from E. coli into the cyanobacterium Anabaena sp.…”
mentioning
confidence: 99%